The Flesh in Pain: A Conversation with John D. Caputo - Mickiewicz, Adriana (Ruch Filozoficzny, 2025)
This article critically examines John D. Caputo’s early ethical project, primarily as described in his work Against Ethics. The central theme of flesh in pain is crucial to his ethical approach. This paper highlights the positive aspects of his work while addressing its potential flaws.